ANALISIS KINERJA SUPPLY CHAIN MANAGEMENT DENGAN PENDEKATAN SCOR PADA CV. DENARA DUTA MANDIRI - Jayanti, Lili; Nurcaya, I Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024, 2024)
Supply Chain Management is a management activity to integrate the supply chain network from suppliers to consumers. The SCOR model is an approach used to determine whether the supply chain network is efficient or not. The purpose of this study was to determine the performance of Supply Chain Management at CV. Denara Duta Mandiri. This research is classified as descriptive research through a quantitative approach using the SCOR Model. Interviews and observations are used as data collection methods. The results of performance measurement using the SCOR method show a POF value of 99.91%, OFCT for 3 days, COGS for 48.43%, and CTCCT for 353 days. This research implies that by applying the Supply Chain Management theory using a good SCOR Model approach, the company can find out the company's current performance compared to similar companies. So that it can make evaluations and improvements in improving its supply chain performance.